HUBUNGAN SELF CARE DIABETES DENGAN KUALITAS HIDUP PASIEN DIABETES MELITUS DI RUMAH SAKIT UMUM MITRA MEDIKAMEDAN TAHUN 2020 - Siregar, Maya Ardilla; Lasmawanti, Sri; Zulfandi, Zulfandi (Jurnal Cakrawala Ilmiah, 2022)
Diabetes mellitus is a collection of symptoms that arise in a person due to an increase in blood sugar (glucose) levels due to absolute or relative insulin deficiency. Objective; The this study aimed to determine the associated diabetes self-care with quality of life for diabetes mellitus patients in Mitra Medika Hospital Medan in 2020. Method; The study used analytic survey method with Cross-Sectional research approach. The population were all Diabetes Mellitus patients at Mitra Medika Hospital Medan, with the sample of 71 respondents. The sampling technique used was accidental sampling. Data was collected using the Self Care and quality of life questionnaire. Data were analyzed using SPSS with the Chi-Square test with p-value of 0.478. Resuls;The results used the Chi-Square test with the results obtained by the p-value=.4780.05. which is no correlation between self-care diabetes and quality of life in diabetes mellitus patients at Mitra Medika Hospital in Medan in 2020, the majority of diabetes mellitus patients at the Mitra Medika Hospital in Medan. The most of diabetes mellitus patients were 56.5% women aged 47-60 years old. Patient with disobedient self care and poor quality of life amounted 59.2%.Consclusion: The conclusion in this study showed that statistically there is no correlation between diabetes self care and the quality of life of diabetes mellitus patients at Mitra Medika Hospital in Medan in 2020